Carl's Masquerade - Day, Alexandra (New York : Farrar, Straus, and Giroux, 1992)
Carl, a large dog, and the baby in his charge fit right in when they follow Mom and Dad to a PTA masquerade party.
Booklist
Sch Libr Jnl
Kirkus
Publ Weekly
Keywords: Dogs -- Fiction; Babies -- Fiction; Parties -- Fiction; Stories without words